Simplifying understory complexity in oil palm plantations is associated with a reduction in the density of a cleptoparasitic spider, Argyrodes miniaceus (Araneae: Theridiidae), in host (Araneae: Nephilinae) webs. Issue 3 (3rd January 2018) - Spear, Dakota M.; Foster, William A.; Advento, Andreas Dwi; Naim, Mohammad; Caliman, Jean‐Pierre; Luke, Sarah H.; Snaddon, Jake L.; Ps, Sudharto; Turner, Edgar C.
Abstract: Expansion of oil palm agriculture is currently one of the main drivers of habitat modification in Southeast Asia. Habitat modification can have significant effects on biodiversity, ecosystem function, and interactions between species by altering species abundances or the available resources in an ecosystem. Increasing complexity within modified habitats has the potential to maintain biodiversity and preserve species interactions. We investigated trophic interactions between Argyrodes miniaceus, a cleptoparasitic spider, and its Nephila spp . spider hosts in mature oil palm plantations in Sumatra, Indonesia. A. miniaceus co‐occupy the webs of Nephila spp . females and survive by stealing prey items caught in the web. We examined the effects of experimentally manipulated understory vegetation complexity on the density and abundance of A. miniaceus in Nephila spp . webs. Experimental understory treatments included enhanced complexity, standard complexity, and reduced complexity understory vegetation, which had been established as part of the ongoing Biodiversity and Ecosystem Function in Tropical Agriculture (BEFTA) Project. A. miniaceus density ranged from 14.4 to 31.4 spiders per square meter of web, with significantly lower densities found in reduced vegetation complexity treatments compared with both enhanced and standard treatment plots. A. miniaceus abundance per plot was also significantly lower in reduced complexity than in standard and enhanced complexity plots. Synthesis and applications : Maintenance of understory vegetation complexity contributes to the preservation of spider host–cleptoparasite relationships in oil palm plantations. Understory structural complexity in these simplified agroecosystems therefore helps to support abundant spider populations, a functionally important taxon in agricultural landscapes. In addition, management for more structurally complex agricultural habitats can support more complex trophic interactions in tropical agroecosystems. Abstract : We examined the effects of experimentally manipulated understory vegetation complexity in oil palm plantations on the density and abundance of the cleptoparasitic spider Argyrodes miniaceus in the webs of Nephila spp. spider hosts. A. miniaceus density per web and abundance per plot were significantly lower in reduced vegetation complexity treatments compared with both enhanced and standard treatment plots. Our results suggest that understory structural complexity in simplified tropical agricultural landscapes can help to support abundant spider populations, a functionally important taxon in agricultural landscapes, and can support more complex trophic interactions in tropical agroecosystems.